Feminist Collections, v.14, no.4 (summer 1993) - (:unkn) unknown (My University, 1993)
Subtitle: A Quarterly of Women's Studies Resources. 42p.
FROM THE EDITORS. BOOK REVIEWS: Being Seen and Heard: Women With Disabilities Speak Out by Deborah Kent.[Reviews] Eleven books on women's experiences with disabilities, from deafness to paraplegia, from learning to speak with one's eyes to expressing sexuality and dealing with pregnancy. Violence Against Women: Gathering Voices by Lori L. Kondora.[Reviews] Violence Against Women: The Bloody Footprints ed. by Pauline B. Bart and Eileen Geil Moran; Sanctions and Sanctuary: Cultural Perspectives of the Beating of Wives ed. by Dorothy Ayers Counts et. al.; What's a Nice Girl Like You Doing in a Relationship Like This?: Women in Abusive Relationships ed. by Kay Marie Porterfield; and Intimate Violence: Interdisciplinary Perspectives ed. by Emilio C. Viano. Images of Native American Girls and Women for Young Readers by Debra Goding. Among the titles: Nobody by Meguido Zola and Angela Deveume, Two Pairs of Shoes by Esther Sanderson, A Friend Called "Chum" by Bernelda Wheeler. FEMINIST VISIONS: The Article You Want When You Want it: An Introduction to Document Delivery Services by Judith Pryor and Ann Margaret Scholtz. RESOURCE ROUNDUP: WOMEN WITH DISABILITIES: By Deborah Kent. Descriptions of five films/videos and five periodicals. WOMEN IN THE RURAL ECONOMY: A RICHLAND COUNTY VIDEO PROJECT: By Linda Shult. COMPUTER TALK: Email discussion lists, databases, and electronic journals. FEMINIST PUBLISHING: Virago celebrates 20 years of publishing; Bookslinger ceases distribution. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Works on abortion, American women in the armed forces, the Canadian women's movement, feminist theory, US government documents, American women playwrights, HD, Louisiana women writers, American women songwriters, prostitution, Latin American and Caribbean women, Asian and Pacific women in the economy, Pakistani women, and Lizzie Borden. (Reviewed by Phyllis Holman Weisbard.) PERIODICAL NOTES: New and newly discovered periodicals on women of African descent, gender and the law, Catholic women in higher education, women workers in the Asia Pacific area, Guerrilla Girls activites, midlife women, Scandinavian women's research, nursing history, cartoons and humor, women in development, preparation for the Fourth World Conference on women, and Japanese women. Special issues of periodicals on arrest in domestic assault cases, women and men in the media, gender in the family court process, history and feminist theory, professional communication, Brazilian women, feminist pedagogy, Katherine Anne Porter, contemporary French feminist writing, and gender stratification in the workplace. Anniversary issue: The Tribune celebrates its 50th issue. Ceased publications: Feminisms. (Compiled by Linda Schult.) ITEMS OF NOTE: Stanton/Anthony papers on microfilm, a pamphlet on fair treatment of girls, a list of books with active female protagonists, a bias-free language guide, a book series on feminist issues, a German women's media bureau, resources for information on equal treatment of the sexes in Europe, and reports on women's health research and on women faculty and students in Canadian universities. (Compiled by Lisa Kaiser.) BOOKS RECENTLY RECEIVED. SUPPLEMENT: INDEX TO FEMINIST COLLECTIONS, VOL. 14.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews